Mechanical and Durability Performance of High-Strength Concrete with Waste Tyre Steel Fibres - Daudi Salezi Augustino; Richard Ocharo Onchiri; Charles Kabubo; Christopher Kanali (Advances in Civil Engineering, 2022)
Concrete with various fibres has been in practice over the years now to improve the internal characteristics of concrete. In most of the developing countries, there is a high rate of waste tyres due to the importation of used cars. Waste tyres increase the environmental burden due to their resistance to decomposition in landfills. To have alternative disposal of waste tyres, their components of steel fibres were utilized in concrete to assess their effect on the mechanical and durability performance of high-strength concrete with a target mean strength of 70 MPa. Fibres had a diameter of 1.3 mm and lengths of 30, 50, and 60 mm with fibre contents of 0.3, 0.5, 0.75, and 1.0% in each length. Slump tests were performed on fresh concrete with and without fibres. The mechanical performance variables assessed were compressive strength, splitting tensile strength, flexural strength, flexural toughness, residual strength, static modulus, and Poisson’s ratio. In addition, durability tests such as chloride ion penetration and absorption rate of water were investigated. The results showed that an increase in fibre length to 60 mm and a 1.0% fibre content resulted in the high bond strength in the concrete matrix resulting in a smaller crack width. Moreover, these fibre length and content resulted in improved tensile and flexural strength to 21.5% and 71.1% of control mix, respectively. The increase in fibre length and content affected both the durability properties and the flowability of the concrete, and as for length (60 mm) and 1% content, concrete had a slump of 77.8% lesser compared to the control mix. The compressive strength was improved to 15.2% for concrete with a fibre length of 50 mm and a fibre content of 0.5%. However, further increases in fibre content and length caused an increase in the number of weaker interfacial transition zones at the composite interface that reduces compressive stiffness, resulting in low compressive strength. Furthermore, the reduced fibre content and length (30 mm) improve the static modulus linearly up to 0.75% fibre content; however, concrete with a fibre length of 50 mm and content of 0.3% gives the best results.